(untitled) (ACME, 2024)
In the field of musicology, among Pietro Bembo’s literary output only the Prose della volgar lingua constantly attracted the attention of scholars, who, since the end of the 1960s, have questioned the appropriateness of applying the linguistic theories enunciated therein to the secular music works of the time. Bembo’s Rime and Stanze, instead, aroused little interest, passing almost unnoticed, despite being set to music by a number of composers throughout the sixteenth century. In an attempt to fill at least part of this gap, this contribution focuses on the Cinquanta stanze del Bembo by Jacques du Pont, a collection that is particularly significant for the circumstances related to its genesis and, above all, for the singularity of some textual variants that render it a very intriguing source for the reconstruction of the literary tradition of Bembo’s poem.